The Effect of Motive Fulfilment as a Meditating Variable between Perceived Organisational Support and Volunteers’ Affective Commitment in Non-Profit Organisations - Usadolo, Queen Emwenkeke; Usadolo, Sam Erevbenagie (African Journal of Inter/Multidisciplinary Studies, 2021)
In this paper, the influence of organisational factors and the role of individual factors on affective commitment is examined, particularly whether volunteers’ motive fulfilment mediates the influence of perceived organisational support on volunteers’ affective commitment. A cross-sectional survey was used to collect data from 213 volunteers from five non-profit organisations in Queensland, Australia. Perceived organisational support is found to have a significant relationship with volunteers’ affective commitment. Furthermore, motive fulfilment has a significant effect on the impact of perceived organisational support (POS) on the outcome. The results of the study provide new knowledge about the importance of motive fulfilment as a tool for improving volunteers’ positive experiences of an organisation and explain how motive fulfilment promotes increased affective commitment.